2019
DOI: 10.3390/ma13010141
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of Municipal Solid Waste Incineration Fly Ash through Co-Mechanical Treatment with Circulation Fluidized Bed Combustion Fly Ash

Abstract: This study aims to explore the solidification performance of municipal solid waste incineration fly ash (MSWIFA) through co-mechanical treatment with circulation fluidized bed combustion fly ash (CFBCFA). The mineral characterization, physical properties, and leaching resistance of the solidified bodies are investigated by X-ray diffraction spectroscopy (XRD), Fourier transform infrared spectroscopy (FT-IR), Thermogravimetry-differential thermal analysis (TG-DTA), compressive strength, porosity, and leaching t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Thus, the recovery process through recycling or other more sustainable methods can reduce the environmental impact of metal production. Additionally, metal recovery requires less energy compared to extracting metals from ore, leading to lower energy consumption and carbon emissions . The Global molybdenum reserve base in 2022 was 12000000 mt, with distribution predominantly from Chile, Peru, U.S.A., and China .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the recovery process through recycling or other more sustainable methods can reduce the environmental impact of metal production. Additionally, metal recovery requires less energy compared to extracting metals from ore, leading to lower energy consumption and carbon emissions . The Global molybdenum reserve base in 2022 was 12000000 mt, with distribution predominantly from Chile, Peru, U.S.A., and China .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, metal recovery requires less energy compared to extracting metals from ore, leading to lower energy consumption and carbon emissions. 14 The Global molybdenum reserve base in 2022 was 12000000 mt, with distribution predominantly from Chile, Peru, U.S.A., and China. 4 This critical aspect in the supply chain stability and recovering metals from existing sources can help to ensure a stable supply of metals by reducing reliance on a sole ore source (International Molybdenum Association reported that global molybdenum extracted in 2022 was 286440 tonnes from mine production only and does not include material recovered from spent catalysts).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, with the depletion of high-grade natural ore reserves, recycling industrial waste can serve dual purposes. It not only allows for the utilization of waste as alternative materials to incorporate bulkily in existing matrices (building materials for instance) but also enables energy-efficient recovery of metals . A notable example is Boliden Rönnskär, a Swedish company that found the energy required to extract metals from e-waste was only 10 to 15% compared to smelting and refining metal ore concentrates .…”
Section: Introductionmentioning
confidence: 99%
“…It not only allows for the utilization of waste as alternative materials to incorporate bulkily in existing matrices (building materials for instance) but also enables energy-efficient recovery of metals. 57 A notable example is Boliden Ronnskar, a Swedish company that found the energy required to extract metals from e-waste was only 10 to 15% compared to smelting and refining metal ore concentrates. 5 Similarly, the efficient extraction of Cr from industrial waste like steel slag can resolve environmental issues while producing valuable products such as Na 2 Cr 2 O 7 and Cr 2 O 3 , widely used in several industrial sectors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are three main methods for solidifying heavy metals in MSWI fly ash, including electrochemical extraction [ 6 , 7 ], solidification by cementitious materials [ 8 , 9 , 10 ], and melting vitrification [ 11 , 12 , 13 ]. Solidification by cementitious materials is considered the most suitable method for MSWI fly ash because of its simple treatment and sound economic and environmental effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%